Differential nasal swab cytology represents a valuable tool for therapy monitoring but not prediction of therapy response in chronic rhinosinusitis with nasal polyps treated with Dupilumab - Danisman, Zeynep; Linxweiler, Maximilian; Kühn, Jan Philipp; Linxweiler, Barbara; Solomayer, Erich-Franz; Wagner, Mathias; Wagenpfeil, Gudrun; Schick, Bernhard; Berndt, Sabrina (Frontiers in Immunology, 2023)
Introduction Chronic Rhinosinusitis with nasal polyps (CRSwNP) is a common chronic disease with a high impact on patients’ quality of life. If conservative and surgical guideline treatment cannot sufficiently control disease burden, biologicals can be considered as a comparably new treatment option that has revolutionized CRSwNP therapy since the first approval of Dupilumab in 2019. With the aim to select patients who benefit from this new treatment and to find a marker for therapy monitoring, we investigated the cellular composition of nasal mucous membranes and inflammatory cells of patients suffering from CRSwNP and undergoing Dupilumab therapy using non-invasive nasal swab cytology. Methods Twenty CRSwNP patients with the indication for Dupilumab therapy have been included in this prospective clinical study. In total, five study visits were conducted with ambulatory nasal differential cytology using nasal swabs starting with the beginning of therapy and followed by visits every 3 months for 12 months. First, these cytology samples were stained with the May-Grunwald-Giemsa method (MGG) and the percentage of ciliated cells, mucinous cells, eosinophil cells, neutrophil cells, and lymphocytes was analyzed. Secondly, an immunocytochemical (ICC) ECP-staining was performed to detect eosinophil granulocytes. Additionally, during each study visit the nasal polyp score, SNOT20 questionnaire, olfactometry, the total IgE concentration in peripheral blood as well as the eosinophil cell count in peripheral blood were recorded. The change of parameters was evaluated over one year and the correlation between clinical effectiveness and nasal differential cytology was analyzed. Results In both MGG (p<0.0001) and ICC analysis (p<0.001) a significant decrease of eosinophils was seen under Dupilumab treatment. When patients were divided into a Eo-low- (<21%) and Eo-high- (≥21%) group according to the percentage eosinophils in nasal swab catology in the first study visit, the Eo-high-group showed a greater change of eosinophils over time (Δ17.82) compared to the Eo-low-group (Δ10.67) but, however, no better response to therapy. The polyp score, SNOT20 questionnaire, and total IgE concentration in peripheral blood showed a significant decrease during the observation period (p<0.0001). Discussion Nasal swab cytology as an easy-to-apply diagnostic method allows detection and quantification of the different cell populations within the nasal mucosa at a given time. The nasal differential cytology showed a significant decrease of eosinophils during Dupilumab therapy and can therefore be used as non-invasvive method for monitoring therapy success of this cost intensive therapy and potentially can allow an optimized individual therapy planning and management for CRSwNP patients. Since the validity of initial nasal swab eosinophil cell count as a predictive biomarker for therapy response was limited in our study, additional studies including larger number of participants will be necessary to further evaluate the potential benefits for clinical practice of this new diagnostic method.